Multiple epiphyseal dysplasia: A diagnostic challenge with genetic heterogeneity - Dasar, Tugba Nur; Taskiran, Ekim; Urel\\-Demir, Gizem; Karaosmanoglu, Beren; Imren, Gozde; Yilmaz, Guney; Alanay, Yasemin; Utine, Gulen Eda; Boduroglu, Koray; Simsek\\-Kiper, Pelin (SPRINGERNATURE, 2023)
55th European-Society-of-Human-Genetics (ESHG) Conference, Vienna, AUSTRIA, JUN 11-14, 2022